Substituent effect of Cp2TiCl2 catalyst for ethylene polymerization: A DFT study - Kefeng Xie; Wei Hao; Shengyuan Xu; Jie Wang; Xiong Wang; Zhengang Han (Polyolefins Journal, 2023)
The substituents on cyclopentadienyl (Cp) can regulate the electronic effect and hindrance of the active center in the metallocene catalyst. This modification can greatly change the catalytic activity of the catalyst and affect some features of the polymer. In order to study the effect of alkyl substituents on Cp in the performance of a typical metallocene catalyst Cp2TiCl2 for ethylene polymerization, two types of catalyst active centers were designed, including non-bridge Cp2(R)TiCH3]+ and bridge [NCP2 (R)TiCH3]+ (R = H, Me, iPr). The effects of alkyl substituent steric hindrance were explored by density functional theory on the complex of catalyst active center with ethylene and the formation of transition state. The results showed that the increase of substituent steric hindrance was unfavorable to complex between ethylene monomer with catalyst active center. Moreover, the bigger alkyl substituent, the greater the activation energy of ethylene insertion into catalyst active center and the more difficult is ethylene polymerization. Therefore, the performance of metallocene catalysts could be regulated by the substituent on Cp.